The Influence Of Domestic Investment, Foreign Investment, And Road Infrastructure Development On Economic Development Inequality In 8 Indonesian Provinces In 2013-2022 In The Perspective Of Islamic Economics - Janah, Selin Puspo; Etika, Citra; Bahtiar, Muhammad Yusuf (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to determine the effect of domestic investment, foreign investment, and road infrastructure development on economic development inequality in 8 Indonesian provinces in 2013-2022 in the perspective of Islamic economics. The analysis was carried out by first calculating the Williamson Index as an indicator of inequality in economic development between regions. This research method uses a statistical panel data approach to the model Fixed Effect Model (FEM). This study explains that domestic investment and foreign capital planting have a positive and significant effect on economic development inequality. While the development of road infrastructure does not affect the inequality of economic development.